Access to healthcare: obstacles, challenges, and the need for territorial equity. The case of al Haouz province. Morocco - Salima Salhi; Bouirbiten Salah; Wafaa Benhsain (Geografares, 2023)
This paper discusses the barriers to access to health care in the province of Al Haouz in Morocco, the challenges that arise from this, and how to meet the requirements of territorial equity. The approach used is geographical, adopting quantitative methods and a cartographic representation of the data to analyze the situation. The results show that geographical and socio-economic factors hinder access to health care, notably the difficult terrain, the unequal distribution of health services, the lack of resources and persistent poverty. These problems remain a major challenge in Al Haouz province despite the Moroccan government’s efforts to improve access to health care. A redefinition of public health system policies is therefore needed, through a strategy developed based on local specificities, including the development of mobile health programs, health professional training, health awareness and investment in new health facilities. They also require reducing direct household spending on health care and expanding health insurance programs.